Outcomes of extra-cranial stereotactic body radiotherapy for metastatic colorectal cancer: Dose and site of metastases matter. (January 2020) - Thompson, Robert; Cheung, Patrick; Chu, William; Myrehaug, Sten; Poon, Ian; Sahgal, Arjun; Soliman, Hany; Tseng, Chia-Lin; Wong, Shun; Ung, Yee; Beatriz Kinupe Abrahão, Ana; Erler, Darby; et al.
Highlights: Higher SBRT doses result in better local control for colorectal metastases. Liver metastases independently have worse local control compared to other sites. A good proportion of patients did not have a change in systemic therapy after SBRT. Abstract: Background and purpose: To review the clinical outcomes following the use of stereotactic body radiotherapy (SBRT) in patients with metastatic colorectal cancer (mCRC) from a large academic institution. Materials and methods: Patients with mCRC treated with extracranial SBRT between 2008 and 2016 were identified from an institutional database. Treatment indications were oligometastases, oligoprogression, and local control of dominant tumors. Endpoints included local progression (LP), overall survival (OS), progression-free survival (PFS), and cumulative incidence of starting or changing systemic therapy (SCST). Univariate and multivariable analyses (MVA) were performed to identify predictive factors. Results: One hundred and sixty-five patients (262 lesions treated) were included. The 2-year cumulative incidence of LP was 23.8%. Lower SBRT doses and tumor location in the liver were significant predictors of LP on MVA. Median OS was 49.3 months, 19.3 months, and 9.0 months for oligometastases, oligoprogression, and local control of dominant tumors, respectively. Primary tumor not in situ, smaller tumors, fewer lines of previous systemic therapy, lower CEA, and oligometastases treatment indications were significant predictors of higher OS on MVA. For the entire cohort, median PFS was 9.9 months, while oligometastatic patients had a median PFS of 12.4 months. 2-year cumulative incidence of SCST was 41.7%. Conclusions: Survival outcomes are favorable after SBRT for mCRC patients. A significant proportion of patients did not have a change in systemic therapy after SBRT. Higher doses are required to obtain the best local control. Efforts should be made to better optimize SBRT delivery for liver metastases given their higher local failure rate.